Indonesian Language Planning in the Education Sector - Yudo Purwono, Prahoro (Universitas Ahmad Dahlan, 2025)
The changes in the Indonesian language within the education sector reflect its dynamic and ever-evolving nature. These changes should be planned and directed to foster a linguistically literate and intellectual younger generation. This research aims to outline the steps or proposals in Indonesian language planning in the education sector based on language change phenomena found. This study uses a qualitative approach and content analysis to explore language change and formulate a conceptual framework for Indonesian language planning in the education sector. It focuses on key aspects of language planning: selection, codification, elaboration, and dissemination by analyzing various written documents such as journal articles, textbooks, and policy papers. Data is collected using documentation techniques to access diverse perspectives and information sources. The analysis identifies language change phenomena, develops a proposed framework based on Haugen & Tauli’s theory, outlines strategic planning stages, and concludes with key insights. The results of the study indicates that Indonesian language planning in the education sector requires collaboration among stakeholders to develop Indonesian as a language of science. The processes of selection, codification, elaboration, and dissemination must be carefully planned over short-, medium-, and long-term periods. Key actors include the Language Agency, Ministry of Education, academics, professional bodies, media, and the public. Ongoing evaluation and revisions are essential to maintain the program's effectiveness. This research contribution also serves as a reference for the government to take initial steps by forming a cross-sector task force, providing funding, promoting teacher training, increasing public awareness, and strengthening cooperation with the media.